Brand Management - An OCBC Bank Case Study - Mohamad Rodzi, Mohd Shahreeman (2009)
The objective of this study is know in detail OCBC Bank (M) Berhad's brand management initiatives as part of its strategy to remain competitive and to develop the brand equity.